Food Systems in an Unequal World : Pesticides, Vegetables, and Agrarian Capitalism in Costa Rica - Galt, Ryan E., 1977- (Book collections on Project MUSE., 2014)
"Food Systems in an Unequal World examines regulatory risk and how it translates to and impacts farmers in Costa Rica. Ryan E. Galt shows how the food produced for domestic markets lacks regulation similar to that of export markets, creating a dangerous double standard of pesticide use"--